Analisis Cost-Volume-Profit Berbantuan Aplikasi Microsoft Excel sebagai Alat Perencanaan Laba pada Konveksi Manz Jaya Abadi - Hidayat, A'rifa Ghassani; Burhany, Dian Imanina (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Micro Small and Medium Enterprises (MSMEs) are a part of the Indonesian economy that has great potential to improve people's welfare. The main objective in establishing a MSMEs is to obtain maximum profit. Many SMEs have not achieved maximum profit because they do not do profit planning. Manz Jaya Abadi Convection is one of the MSMEs that has not yet made profit planning. The purpose of this reasearch is to conduct profit planning using cost-volume-profit (CVP) analysis assisted by microsoft excel application. The type of research used is descriptive using analytical tools such as contribution margin, break-even point, sales analysis, margin of safety, degree of operating leverage and multi-product break-even point at Manz Jaya Abadi Convection. The result of this study is the design of applications using Microsoft Excell to assist in conducting CVP analysis as a profit planning tool that can be used regardless of time and product type.